A hydrometallurgical process for recovering total metal values from waste monolithic ceramic capacitors. (June 2016) - Prabaharan, G.; Barik, S.P.; Kumar, B.
Highlights: Commercially feasible hydrometallurgical process for recycling industries. More than 99% of leaching efficiency was achieved. Simple and easy method of separation and purification of Ba, Ti, Sn, Cu and Ni. Overall recovery of precious metals and base metals were 92% and 95%, respectively. Flow sheet proposed for commercial application. Abstract: A hydrometallurgical process for recovering the total metal values from waste monolithic ceramic capacitors was investigated. The process parameters such as time, temperature, acid concentration, hydrogen peroxide concentration and other reagents (amount of zinc dust and sodium formate) were optimized. Base metals such as Ba, Ti, Sn, Cu and Ni are leached out in two stages using HCl in stage 1 and HCl with H2 O2 in stage 2. More than 99% of leaching efficiency for base metals (Cu, Ni, Ba, Ti and Sn) was achieved. Precious metals such as Au and Pd are leached out using aquaregia and nitric acid was used for the leaching of Ag. Base metals (Ba, Ti, Sn, Cu and Ni) are recovered by selective precipitation using H2 SO4 and NaOH solution. In case of precious metals, Au and Pd from the leach solution were precipitated out using sodium metabisulphite and sodium formate, respectively. Sodium chloride was used for the precipitation of Ag from leach solution. Overall recovery for base metals and precious metals are 95% and 92%, respectively. Based on the results of the present study, a process flow diagram was proposed for commercial application.